Genetic Diversity of Boleophthalmus Boddarti and Other Malaysian Gobies - Mohammadi, Mehdi (2007)
Mudskippers (Family Gobiidae: Subfamily Oxudercinae) are residents of tidal mudflat shores, tidal muddy zone of estuaries, rivers, and mangrove swamps. The aims of this study were to describe the morphological and genetic variations among populations of Boleophthalmus boddarti, phylogenetic of Malaysian Oxudercine gobies, and the exposure of PAHs on Boleophthalmus boddarti. The samples of B. boddarti were collected from six locations, namely Pulau Pinang, Selangor (Kuala Selangor), Negeri Sembilan (Pasir Panjang), Melaka, Johor and Pahang (Cherating). Conventional and Truss morphometrics analyses were carried out on 300 individuals belonging to 7 species, namely B. boddarti, Periophthalmus chrysospilos, Periophthalmus grasilos, Periophthalmus novemoradiatus, Periophthalmodon schlosseri, Pseudapocryptes elangatus and Scartlaos histophoris. Using the Discriminate Function Analysis (DFA), the conventional morphometric discriminate the populations of B. boddarti into 2 groups while Truss morphometrics into 3 groups, whereby geographically closer populations were grouped together. Of the 29 Randomly Amplified Polymorphic DNA (RAPD) primers tested, only 12 primers gave clear bands and showed polymorphisms. Eleven bands were identified as RAPD markers in the six populations (N=155) of B. boddarti. The dendrogram from RAPD data revealed three major groups of B. boddarti, in which the first group consisted of the central population (Selangor, Negeri Sembilan and Melaka populations), the second group made up the southern (Johor) and eastern (Pahang) populations, and the third group was the northern populations (P. Pinang), which was distinctly separated from the rest of the population, with a genetic distance of 0.698. The mitochondrial cytochrome b (cytb) sequences in 6 populations of B. boddarti revealed a total of 26 haplotypes. Based on haplotype analyses, the populations were grouped into two clades, I and II. Clade I was divided into two subclades consisting of the northern (P. Pinang) and the central (Selangor) populations as subclade IA, and the central population (N. Sembilan and Melaka) as subclade IB. Clade II consisted of the southern (Johor) and the eastern (Pahang) populations of B. boddarti. Both cytb (345bp) and 16S rDNA (550bp) gene sequences were carried out for phylogenetic studies on 11 species of the subfamily Oxudercinae. Four phylogenetic trees were constructed using maximum parsimony (MP) and neighbor-joining (NJ) methods, using Kimura-2-Parameter (K2P) and Jukes and Cantor models. Based on parsimony analysis, Oxudercinae subfamily was divided into two main clades consisting of Oxuderces in one clade and the rest were in another clade. The distributions of polycyclic aromatic hydrocarbons (PAHs) in both sediments and porewaters (N=8) in the Klang River and its estuaries were higher than those in the Kuala Muda River. Hepatic EROD activities were carried out on B. boddarti (N=62) collected from the Klang River and its estuaries as polluted and Kuala Muda River as less polluted rivers. Hepatic EROD activities showed significantly (p<0.05) higher induction of EROD in fish from the Klang River and its estuaries (mean=24.55 pmol min-1 mg protein-1) than those in the Kuala Muda River (mean=6.84 pmol min-1 mg protein-1). There were close relationships between the log EROD activities in B. boddarti and the total PAHs concentration in sediments (r2= 0.68) and porewaters (r2= 0.66), implying that this fish can be used as an early signal of PAHs exposure in estuarine areas. In conclusions, morphological and molecular markers using both RAPD mtDNA were able to discriminate the populations of B. boddarti in Peninsular Malaysia. MtDNA sequences (cytb and 16S rDNA) were found to be useful tools for phylogenetic studies of the subfamily Oxudercinae. For future endeavour, the use of the other molecular markers is recommended to study the population structure of mudskippers in Malaysia.